2002
DOI: 10.1116/1.1459723
|View full text |Cite|
|
Sign up to set email alerts
|

Chiral pattern formation: Combined transmission electron microscopy and atomic force microscopy study of tetracyanoquinodimethane thin film grown by vacuum evaporation

Abstract: Organic nanowires and quasi-two-dimensional chiral patterns of tetracyanoquinodimethane have been successfully generated by vacuum thermal evaporation. The nanowires and patterns were characterized by using atomic force microscopy and transmission electron microscopy. The influence of electric charged clusters, deposition rate, and substrate temperature were experimentally investigated. Contrary to previous reports, charged clusters are found to be unnecessary to the chiral pattern formation. It was shown that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Micro-and nano-crystals of TCNQ have been previously observed with several different structures; for example, helical nanowires and dendrites of complexes with TTF and Ag-TTF have been reported in several works, [12,13] and, depending on solute concentration, TCNQ films on Cu and Al form structures that are dendritic or rhombic. [14] Vacuum-evaporated TCNQ has also been observed with chiral patterns by Li et al [15] However, as shown in Fig. 1, we observed an extremely wide variety of TCNQ crystal habits at several different size scales in samples prepared using reprecipitation.…”
Section: Resultssupporting
confidence: 73%
“…Micro-and nano-crystals of TCNQ have been previously observed with several different structures; for example, helical nanowires and dendrites of complexes with TTF and Ag-TTF have been reported in several works, [12,13] and, depending on solute concentration, TCNQ films on Cu and Al form structures that are dendritic or rhombic. [14] Vacuum-evaporated TCNQ has also been observed with chiral patterns by Li et al [15] However, as shown in Fig. 1, we observed an extremely wide variety of TCNQ crystal habits at several different size scales in samples prepared using reprecipitation.…”
Section: Resultssupporting
confidence: 73%
“…At a rate of 0.37 Å s À1 , randomly oriented islands with a size up to 10 mm are obtained, and the coverage is relatively inhomogeneous. The croissantlike shape exhibited by the islands compares well with the spiral appearance of C 60 -TCNQ 18,19 and pure TCNQ 20 grown by ionized-cluster-beam and vacuum thermal sublimation, respectively. Fig.…”
Section: Properties Of Tcnq Thin Films On Bare Substratesmentioning
confidence: 53%
“…It reveals that the film has an extended large-scale single-crystal structure, which would be favorable for nanoscale data storage using tip writing/reading technique . It should be pointed out that the high-voltage electron beam in the TEM system could cause the film to convert from crystalline to amorphous in less than 20 s as that observed in other crystalline organic films 4 TEM electron diffraction pattern showing that the DDME thin film is well crystallized. …”
Section: Resultsmentioning
confidence: 85%